Adipose-Derived Neural Stem Cells Combined with Acellular Dermal Matrix as a Neural Conduit Enhances Peripheral Nerve Repair. Issue 9 (September 2019) - Syu, Wei-Ze; Hueng, Dueng-Yuan; Chen, Wei-Liang; Chan, James Yi-Hsin; Chen, Shyi-Gen; Huang, Shih-Ming
Reconstruction to close a peripheral nerve gap continues to be a challenge for clinical medicine, and much effort is being made to develop nerve conduits facilitate nerve gap closure. Acellular dermal matrix (ADM) is mainly used to aid wound healing, but its malleability and plasticity potentially enable it to be used in the treatment of nerve gaps. Adipose-derived stem cells (ADSCs) can be differentiated into three germ layer cells, including neurospheres. We tested the ability of ADSC-derived neural stem cells (NSCs) in combination with ADM or acellular sciatic nerve (ASN) to repair a transected sciatic nerve. We found that NSCs form neurospheres that express Nestin and Sox2, and could be co-cultured with ADM in vitro, where they express the survival marker Ki67. Following sciatic nerve transection in rats, treatment with ADM+NSC or ASN+NSC led to increases in relative gastrocnemius weight, cross-sectional muscle fiber area, and sciatic functional index as compared with untreated rats or rats treated with ADM or ASN alone. These findings suggest that ADM combined with NSCs can improve peripheral nerve gap repair after nerve transection and may also be useful for treating other types of neurological gaps.